2016
DOI: 10.1515/zkri-2016-1934
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscratching meets nanoindentation

Abstract: A specimen of high-carbon nitrogen-doped steel has been synthesized to supplement previous studies on wootz-like steels. A comparison of different states of material as well as one of distinct methods of hardness testing has been performed. Electron microscopy of the specimens’ microstructure revealed nano-structuring similar to that observed with ancient sabers. Part of them was annealed so that the nano-structures dissolved. Nano-hardness values derived under ambient conditions from indentation as well as fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Shakhverdova et al reported an UHCS fabricated by adding an organic compound as the carbon source (copper phthalocyanine, C 32 H 16 CuN 8 ). However, no further discussion about the effect of the organic carbon source on the materials was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Shakhverdova et al reported an UHCS fabricated by adding an organic compound as the carbon source (copper phthalocyanine, C 32 H 16 CuN 8 ). However, no further discussion about the effect of the organic carbon source on the materials was reported.…”
Section: Introductionmentioning
confidence: 99%